Prophetic Ecotheology and the Indonesian Ecological Crisis: A Hadith-Based Approach - Zulfarizal Zulfarizal; Laila Sari Masyhur; Zakiyah Zakiyah; Alven Putra (Jurnal Ushuluddin, 2026)
The ecological crisis, characterized by deforestation, environmental pollution, biodiversity loss, and climate change, has become a serious challenge to the sustainability of human life, including in Indonesia. Although Islamic ecotheological studies have developed considerably, most existing research has focused on Qur'anic perspectives, while the ecotheological dimensions embedded in the Prophetic traditions (hadith) have received relatively limited systematic attention and contextualization in relation to contemporary environmental issues. This study aims to examine the ecological values contained in the hadiths of the Prophet Muhammad and their relevance to addressing Indonesia's environmental crisis. Employing a qualitative approach based on library research, the study draws upon classical hadith collections and relevant secondary sources. The data are analyzed using thematic analysis within the framework of Islamic ecotheology. Particular attention is given to hadiths concerning land management, tree planting, animal welfare, environmental conservation, and the responsible use of natural resources. The findings reveal that the Prophetic traditions embody a comprehensive ecological ethic that positions humans as khalīfah entrusted with maintaining the balance and sustainability of ecosystems. This study offers a hadith-based ecotheological perspective that broadens the discourse of Islamic ecotheology, which has thus far been predominantly centered on the Qur'an. The findings not only enrich contemporary hadith studies but also provide an ethical foundation for strengthening environmental education and fostering ecological awareness among Muslim communities in Indonesia.